Mot bedre vitende i norsk matsektor - Steen, Frode; Pettersen, Ivar (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"The Norwegian food market engenders strong opinions and substantial media attention, with questions regarding agricultural regulations, competition between retail food chains, and the relationship between chains and their suppliers fueling debate. Meanwhile the country's politicians call for greater intervention. Much of the debate can seem to be happening "against our better judgment". Vague assumptions about the state of the food sector, paired with a strong political will to apply initiatives, is reason enough to look closer at the situation. This anthology provides an up-to-date factual assessment of the entire value chain in the food market. Central topics include development of productivity in the various segments of the food chain, price differences between different countries, and effects of Norway's tariff system. The book presents new contributions concerning the structure of the market, access to food stores and the significance of brand names, and especially to the kind of bargaining tactics employed between food chains and suppliers, with an overview of how their negotiations are carried out and possibilities for regulatory measures afforded under existing laws. Against Better Judgment in the Norwegian Food Sector confirms existing knowledge and presents new findings that deserve attention from the sector itself, the media and public authorities. The book will be of interest to everyone seeking to understand the Norwegian food sector and take part in its further development. The book's chapters have been written by seven researchers with lengthy experience in the field, and edited by Frode Steen, a professor in the Department of Economics at the Norwegian School of Economics, and Ivar Pettersen, a senior advisor at the Norwegian Institute of Bioeconomy Research."